The influence of development level of different generations on innovative development - Zhanar Konys (Economic and Environmental Studies (E&ES), 2016)
This paper discusses the influence of development level of generations on innovative development of a country in case of Kazakhstan. Parameters which influence the development level of human capital and innovative development level of a region were determined. Direct influence of human capital on innovative development of a region is proved and the results generalized on national level. Consequently, based on the performed analysis, country's population was divided into three generations. Using official statistics, the influence of the development level of generation on innovative development of the country was proved.
Keywords: O15; O32; 330; developed generation; education; human capital; innovative development; national innovation system